Sosialisasi Penanggulangan Kebakaran Dilingkungan Masyarakat Padat Penduduk - ramdan, muhamad; swandito, adji; Fuadi , Yan; Sunyanti, Sunyanti (EUNOIA, 2023)
This simulation method is very important to be given to trainees to provide the opportunity to practice the training material obtained. It is hoped that the training participants must really master the training material received, know about the causes of fires, know the methods of extinguishing fires in the community, can use a good and correct fire extinguisher. From observations of the results of fire prevention training in densely populated communities, it can be seen that the community participated in the training with great enthusiasm. It was also seen that whenever there was something that was not explained by the speaker, the community immediately asked the speaker, especially the accompanying students. Some small difficulties, a small part of the community is not very familiar with the use of APAR, so they have to teach the basics of its use.